KINERJA BANK PEMBIAYAAN RAKYAT SYARIAH DI SUMATERA BARAT DENGAN MENGGUNAKAN MAQASHID SYARIAH INDEX - AIDIL NOVIA (Maqdis: Jurnal Kajian Ekonomi Islam, 2020)
The paper aimed to analyze Islamic Rural Banks (BPRS) performance in West Sumatera with maqashid syariah indeks (MSI) model. Quantitative approach used in this research, using Sekaran Operationalization Method and Islamic Maqashid Syariah Index (MSI) model established by Mustafa Umar. There were 3 indicators in this Maqashid Syariah Index (MSI): educating the individual (Tahdhib al-Fard), establishing justice (Iqamah Al-Adl) and public interest (Jalb al-Maslahah). The study found that generally maqashid shariah index (MSI) was above 50%. The ranking of BPRS performance from the highes to the lowest were: BPRS Al Makmur (73,54%), BPRS Haji Miskin (71,5%), BPRS Gajah Tongga Kota Piliang (71%),  BPRS Barakah Nawaitul Ikhlas (67,35%), BPRS Ampek Angkek Canduang (66,3%, BPRS), Mentari Pasaman Saiyo (60,87%), and BPRS Carana Kiat Andalas (60,77%).